ANALISA SIFAT ELEKTROKIMIA ELEKTRODA SUPERKAPASITOR BERBASIS KARBON AKTIF DARI KULIT SINGKONG - Eva Wahyuni Harahap; Eman Taer; Ari Sulistyo Rini (Universitas Riau, 2023)
Another problem from technological developments and advancements is the increase in population which causes increasingly complex waste management problems. One type of urban waste is waste caused by industrial waste such as waste from processing cassava or cassava. The use of cassava peel as a precursor of activated carbon with a high specific capacitance value has been proven. The resulting carbon powder is converted in the form of pellets or monoliths using a hydraulic press without the addition of adhesives. The carbonization process is carried out from room temperature to 600°C in an N2 gas environment, while the physical activation process is carried out from 600°C to a high temperature of 850°C in a CO2 gas environment. Density analysis was reviewed as an initial evaluation of porous carbon electrodes. Furthermore, the electrochemical properties of the supercapacitor were evaluated through three different techniques including cyclic voltammetry (CV), galanostatic charge discharge (GCD) and electrochemical impedance spectroscopy (EIS) techniques in a two-electrode system in 1 M H2SO4 electrolyte. The results of the research have obtained carbon electrodes from cassava peel waste through chemical and physical activation processes. After testing the electrochemical properties of the supercapacitor electrode, the specific capacitance value of the supercapacitor cell on the chemical activator ZnCl2 with a concentration of 0.3 M and 0.7 M, respectively, was 196 F/g, 176.7 F/g in the CV method of 183.62 F/g, 147.64 F/g on the GCD method and 135 F/g, 126.6 F/g on the EIS method. These results confirm that the cassava peel has the potential to be used as a porous activated carbon for the base material for supercapacitor electrodes.